(untitled) (Global Journal of Management and Business Research, 2012)
This paper analyzes business process re-engineering (BPR) implementation at Ethiopian higher education institutions (EHEI#x2019;s) i.e., Mekelle University, Mekelle, and Aksum University, Aksum. It investigates the current status and effectiveness of BPR implementations at the EHEI#x2019;s. It reviews the literature relating to the hard and soft factors that cause success and failure for BPR implementations, classifies these factors into subgroups, and identifies critical success and failure factors. Finally, it explains how these factors influence the process of BPR implementation in the higher institutions. Primary data were collected by means of survey questionnaires from academic staff members and interviews with the academics core process owners. One hundred sixty survey questionnaires were distributed to Mekelle (110) and Aksum (50) universities. All the questionnaires were filled and properly received from both universities. The respondents for the survey were all academic staff members from all departments and posts (technical assistant, graduate assistant, assistant lecturer, lecturers and professors). The findings of the research show that the institutions#x2019; performance is not effective in terms communicating and accomplishing the goals and objectives of BPR. The current progress of BPR in the institutions is also at low level. The findings also show that effective utilization of resources, having BPR motivated by customer demands, good information exchange and flow, continuous performance improvement, using technology as enabler not as solution, developing and communicating clear written goals and objectives, proper alignment of BPR strategy with the corporate strategy, using progress evaluation are the most important factors that enable BPR implementation to be successful, whereas lack of employee training, unrealistic report to outsiders that hide actual progress of BPR implementation, management frustration with slow business results, lack of management deter